Effectiveness of Client-Centered Occupational Therapy in Patients With Rheumatoid Arthritis: Exploratory Randomized Controlled Trial - Eda TONGA,; Tülin DÜGER,; Metin KARATAŞ, (Archives of Rheumatology, 2016)
Objectives: This study aims to examine the effectiveness of client-centered occupational therapy in patients with rheumatoid arthritis (RA). Patients and methods: The study included 40 patients (2 males, 38 females; range 39 to 60 years) with RA. Patients were divided into two groups as intervention group (n=20) and control group (n=20) by random sampling method. Each group was given 10 sessions of physical therapy program. In addition, the intervention group received client-centered occupational therapy. Patients were evaluated with Turkish versions of Short-Form McGill Pain Questionnaire, Health Assessment Questionnaire, The Arthritis Impact Measurement Scales 2, RA Quality of Life Questionnaire, and Canadian Occupational Performance Measurement. Results: Pain, activity limitation, and participation restriction scores decreased significantly more in the intervention group compared to the control group. Also, quality of life increased significantly in the intervention group (p<0.05). Conclusion: Our findings suggest that occupational therapy intervention reduces activity limitation and participation restrictions in patients with RA. Therefore, such interventions may be generalized for this patient group.